Differentiation of lard from other animal fats and vegetable oils based on n-Alkane profiles and chemometrics analysis - Sapian, Nur Ain Syaqirah (2019)
Biofilms can be defined as a bacterial communication form, in which the bacteria adhere to surfaces and to each others using slimy, glue-like substances called the extra-cellular matrixes. Production of biofilms is a critical key for the bacteria to express multiple kinds of biological processes, including resistance against sanitizers and environmental stresses. Ramsar hot spring, is an active, radon-containing hot spring situated in north of Iran, has the highest background of natural radiation in the world (260 mGy/year). Investigation of the microbial biofilm formation in these environments may contribute to understand their significance in food industries, in terms of cellular resistance to environmental stresses and to ionizing sterilization methods commonly used for food materials and equipment. In this work, B. subtilis (RAM-04) was isolated from water and mud samples obtained from Ramsar hot spring, and was found to survive following exposure to 20 kGy gamma radiation with a viable growth of 20 CFU/mL. B. subtilis (GAD-28) was isolated from water and biofilm samples obtained from Gadek hot spring, Malaysia, where no dose of natural radiation was reported, and was therefore used as a control. Biofilm Formation assay was performed using Microtitre Plate technique and Scanning Electron Microscopy (SEM). Gene expression analysis to quantify the critical genes involved in B. subtilis biofilm formation was performed using direct sequencing method and quantitative PCR (q-PCR). Biofilm formation under food-related stresses, including incubation time, temperature, pH, nutrient concentration, and subsequent chlorine treatment, was also estimated using the Microtitre Plate technique for both isolates. Results of the Microtitre Plate technique and the Scanning Electron Microscopy showed that RAM-04 formed stronger biofilms compared with GAD-28. In addition, the results of gene expression analysis of RAM-04 revealed that of 13 genes in total, seven genes showed genetic variations at multiple places in the genome sequences. The q-PCR revealed an up regulation of yqxM-sipW-tasA operon genes in RAM-04 with the folding change of 13, 11, and 8 respectively, and a down regulation in both ccpA and slrR genes with the folding change of 0.2 and 0.3 respectively. There was a marked variability in the food-related stress profiling, in which temperature, pH and media concentration showed a significant effect on biofilm formation by both isolates, whereas, chlorine and incubation time had a non-significant effect. As a conclusion, RAM-04 was able to produce a biofilm three times stronger compared to that of GAD-28. In addition, assuming that RAM-04 utilizes the operon yqxM-sipW-tasA to produce the extracellular matrix that is necessary to build such a strong architecture of cell associations or biofilms. This in turn will be potential strategies to survive and resist extreme ionizing environmental stress. However, the biofilm formation under food-related-stress offers possible practical applications, like usage of physical applications (sub-thermal temperatures and nutrient deficiency) to control the development of biofilms in both isolates. On the other hand, the research highlighted the possible disadvantage of chlorine usage as an active sanitizer in food industries.